2018
DOI: 10.2147/ott.s179866
|View full text |Cite
|
Sign up to set email alerts
|

SIRT6 overexpression induces apoptosis of nasopharyngeal carcinoma by inhibiting NF-κB signaling

Abstract: BackgroundPrevious reports show that SIRT6 serves as a critical modulator of the development of multiple malignancies as well as other disorders. However, its role in nasopharyngeal carcinoma (NPC) is unknown. Thus, we elucidated the effects of SIRT6 on the survival of NPC cells, and modulation of cell death.MethodsWe found that expression of SIRT6 is downregulated in ten human NPC specimens as well as in the human NPC cell lines, 5-8 F and CNE1, as compared with that in healthy tissues and normal nasopharynge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Lei et al found that overexpression of SIRT6 might inhibit the expression of NF-κB by means other than acetylation and promoted apoptosis of NPC cells. 113 In addition, knockout of NEAT1, a cancer-related long non-coding RNA, can inhibit the proliferation of NPC cells and promote apoptosis via promoting the activity of the miR-124/NF-κB axis. 114 Deleted in liver cancer-1 (DLC-1) is a member of the GTPase-activating protein (GAP) family that is able to inhibit multiple tumor processes.…”
Section: Crucial Signal Pathways Related To Targeted Therapy Of Npcmentioning
confidence: 99%
“…Lei et al found that overexpression of SIRT6 might inhibit the expression of NF-κB by means other than acetylation and promoted apoptosis of NPC cells. 113 In addition, knockout of NEAT1, a cancer-related long non-coding RNA, can inhibit the proliferation of NPC cells and promote apoptosis via promoting the activity of the miR-124/NF-κB axis. 114 Deleted in liver cancer-1 (DLC-1) is a member of the GTPase-activating protein (GAP) family that is able to inhibit multiple tumor processes.…”
Section: Crucial Signal Pathways Related To Targeted Therapy Of Npcmentioning
confidence: 99%
“…SIRT6 is highly correlated with cell apoptosis. As aforementioned, overexpression of SIRT6 may decrease antiapoptotic Bcl‐2 levels, increase proapoptotic Bax and cleaved caspase‐3 levels, as well as inhibit NF‐κB signaling, thus leading to apoptosis in various tumors such as nasopharyngeal and renal carcinoma 59,114,115 . However, opposite results from Liu et al 116 revealed that SIRT6 was overexpressed in prostate tumors and SIRT6‐KD was beneficial to cancer cell apoptosis and cell cycle arrest, unraveling a oncogenic function of SIRT6 in prostate cancer.…”
Section: Human Diseasesmentioning
confidence: 96%
“…A similar effect was observed also in glioma cells in which SIRT6 suppresses the expression of poly(C)-binding protein 2 (PCBP2) through H3K9 deacetylation at its promoter, hence blocking tumor cell growth [ 59 , 60 ]. Further evidence suggests the tumor suppressor role of SIRT6 in other types of cancer such as hepatocellular carcinoma (HCC) [ 61 ], lung cancer [ 62 ] and nasopharyngeal carcinoma (NPC) [ 63 ], where SIRT6 has been found downregulated at gene level compared to normal tissues. In HepG2 cells, SIRT6 overexpression impairs cancer proliferation through the inhibition of ERK1/2 signaling and promotes apoptosis by inducing increased levels of cleaved caspase-3 [ 61 ].…”
Section: Role Of Sirt6 In Cancermentioning
confidence: 99%
“…In NPC, the NF-κB pathway is particularly active and is involved in the activation of anti-apoptotic proteins such as FLIP, c-IAP1/2 and XIAP, favoring cancer resistance and progression [ 69 ]. Notably, SIRT6 was found to be downregulated in NPC and its restoration led to decreased levels of NF-κB and anti-apoptotic factor Bcl-2, along with augmented expression of pro-apoptosis mediators Bax (Bcl-2 associated X protein) and cleaved caspase-3 [ 63 ].…”
Section: Role Of Sirt6 In Cancermentioning
confidence: 99%